Teacher work in times of pandemic: Worsening inequalities and work intensification in the province of Buenos Aires - Nora Beatriz Gluz; Luisa Vecino; Valeria Martínez-del-Sel (Íconos)
This article is the result of an investigation into the conditions and determinants of teaching at the secondary level in the province of Buenos Aires, Argentina, during the COVID-19 pandemic. The objective is to analyze how gender, technological, and socio-health inequalities intersect in educational work, in a context marked by the intensification of teaching work and widening social gaps. We considered the period between March 2020 and March 2021, and analyzed the following particularities: official regulations, teachers’ working conditions, the composition and social situation of teachers’ households, technological resources available, and institutional support that conditioned pedagogical work. We studied the regulations of the period, official statistics, and surveys and open interviews with secondary school teachers in four municipalities, which reflect the heterogeneity of this Argentine province. Among the findings, we emphasize the intensification of the work of teaching during the pandemic and its particular impact on the secondary level, due to the structure of this job position; among female teachers, the situation became more complex due to asymmetry in the distribution of care work. Collective work emerged to confront these conditions, as an alternative and support mechanism to overcome isolation.